ІВАН ОГІЄНКО - ПРОВІДНА ПОСТАТЬ УКРАЇНСЬКОГО МОВОЗНАВСТВА, КУЛЬТУРИ ТА ІСТОРІЇ ЦЕРКВИ - ЗОРИК, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У даній статі розглянуто творчу, наукову та громадську діяльність видатного науковця, професора Іван Огієнка, «людини праці і обов’язку», «невтомного працівника українського Ренесансу», «ініціатора розвою української культури», філософа й педагога, як його називали сучасники-бібліографи, захоплені його фантастичною працьовитістю. Іван Огієнко був блискучим популяризатором, натхненним пропагандистом культури української мови, літератури, краєзнавства, славістики, філософії, народної архітектури, освіти, бібліографії в ХХ столітті. Зорик В.А. ИВАН ОГИЕНКО – КЛЮЧЕВАЯ ФИГУРА УКРАИНСКОГО ЯЗЫКОВЕДЕНИЯ, КУЛЬТУРЫ И ИСТОРИИ ЦЕРКВИ В данной статье рассмотрена творческая, научная и общественная деятельность выдающегося ученого, профессора Ивана Огиенкo, «человека труда и обязательств», «неутомимого работника украинского Ренессанса, «инициатора рассвета украинской культуры», философа и педагога, как его называли современники-библиографы восхищенные его фантастическим трудолюбием. Иван Огиенко был блестящим популяризатором и пропагандистом культуры украинского языка, литературы,краеведения, славистики, философии, народной архитектуры,просвещения, библиографии в ХХ столетии. Ключевые слова: украинский Ренессанс,спектр.славистика,библиография,приват- доцент,популяризатор,учитель. Zorik V. IVAN OGIENKO- BRIGHT REPRESENTATIVE OF THE UKRAINIAN, CULTURE AND THE HISTORY OF CHURCH This article examines the creative, scientific and public activity of outstanding scientist, professor Ivan Ogienko, “the person of labor and obligations”, “untiring worker of Ukrainian Renaissanse”, “the initiator of the dawn of Ukrainian culture”, philosopher and teacher, as him called contemporaries bibliographers enraptured by his fantastic diligence. Ivan Ogienko was the bright popularizer and the propagandist of the culture of Ukrainian language, literature, regional study, Slav philology, philosophy, folk architecture, education, bibliography in 20th century. The author gives the detailed characteristic of the fundamental periods of the life of scientist,were analyzed the reasons, which influenced the Ogienko’s decision to leave beloved Ukraine.Biography of this patriot and devotee reflected dramatic changes in the political history of the Ukraine in Twentieth century, but it is the model of adherence to one’s duty and to the cause of national science. At the same time Ogienko’s activity pushed and stretched national boundaries and served strengthening the idea of the world value of Ukrainian culture, emphasized the European nature of the nation and contributed to worldwide popularization of all the best that the Ukrainian people acquired within the millenia of the cultural and political development. Keywords: Ukrainian renaissance, spectrum ,slavistiks, bibliography, assistant professor, popularizer, teacher.